2013
DOI: 10.1021/jp405101q
|View full text |Cite
|
Sign up to set email alerts
|

Ordered H2O Structures on a Weakly Interacting Surface: A Helium Diffraction Study of H2O/Au(111)

Abstract: KEYWORDS : Surface structure, water adsorption on metals, water gold interaction, helium atom scattering.! " ! 1 ABSTRACT: In this manuscript we report helium atom scattering (HAS) measurements of the structure of the first H2O layer on Au(111). The interaction between H2O and Au(111) is believed to be particularly weak and conflicting evidence from several indirect studies has suggested that water either grows as 3D ice crystals or as an amorphous wetting layer. In contrast, our measurements show that between… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 32 publications
3
26
0
Order By: Relevance
“…Simultaneously, diffraction peaks emerge at the positions of a graphene lattice, as shown by the red curve in Fig. 2 d. The relative diffraction intensities are identical to the pristine graphene surface (grey dashed curve), which would not be the case for a crystalline ice overlayer 32 . Ice I h and ice I c also have too large a lattice spacing 33 to give rise to this periodicity, even for the spacing in the recently discovered square ice 33 , 34 .…”
Section: Resultsmentioning
confidence: 92%
“…Simultaneously, diffraction peaks emerge at the positions of a graphene lattice, as shown by the red curve in Fig. 2 d. The relative diffraction intensities are identical to the pristine graphene surface (grey dashed curve), which would not be the case for a crystalline ice overlayer 32 . Ice I h and ice I c also have too large a lattice spacing 33 to give rise to this periodicity, even for the spacing in the recently discovered square ice 33 , 34 .…”
Section: Resultsmentioning
confidence: 92%
“…Due to the large cross section of HAS to isolated adsorbates (including hydrogen as described in Section 3.5), the position and structure of hydrogen atoms and adsorbed water layers can be readily determined. [103][104][105] These include also the hydrogenation of a graphene surface 106 while H-positions are hard to determine with other methods (e.g., hydrogen is a weak scatterer for electrons) which also present a severe risk of damaging the H-layer. 107 In a study of highly proton-ordered water structures on oxygen pre-covered Ru(0001) it could be shown that the atomic oxygen and the oxygen from water form a (2 Â 2) surface reconstruction, which however, is broken by the hydrogen to give a (2 Â 4) surface reconstruction: while LEED measured a (2 Â 2), HAS measured a (2 Â 4) superstructure.…”
Section: Nanoscale Surface Topographymentioning
confidence: 99%
“…When used to study surfaces, HeSE experiments can be classified as a subset of quasi-elastic helium atom scattering experiments [26]. Surface-sensitive HeSE experiments [31][32][33] have been used to study surface morphology [36], molecular and atomic surface diffusion [32,33,[37][38][39][40][41], inter-adsorbate forces [38,42], phonon dispersions [32,33,43], phason dispersions [44], structures and phase transitions of ionic liquids [45] and friction between adsorbates and surfaces [46][47][48]. HeSE experiments have provided information about potential energy surfaces [32,33,49] and surface-adsorbate interactions [32,33,50] and are frequently combined with microscopic calculations to both test theory and gain insight into surface-adsorbate interactions [39,51,52].…”
Section: Introductionmentioning
confidence: 99%